PROFIL PEMECAHAN MASALAH POLA BARISAN BILANGAN DITINJAU DARI GAYA KOGNITIF FIELD DEPENDENT DAN FIELD INDEPENDENT DI SMPN 6 PALU - Ayulinansyah, Sri (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2024)
The examination approach utilized is engaging subjective which intends to portray the problem solving profile of understudies at SMPN 6 Palu using FI and FD cognitive styles regarding number pattern sequence material. The research subjects were 2 students from class VIII of SMPN 6 Palu, comprising of high capacity understudies who had a field subordinate kognitif style and high capacity understudies who had a field free kognitif style. Information assortment techniques in this research were assisted by the GEFT test, number sequence pattern test, and interview guide. Information examination methods incorporate information buildup, information show, and reaching determinations. The validity’s data using time triagulation is carried out by collecting data at different times. The results of the research show that subjects with an independent field cognitive style are able to solve problems carrying out all stages of Polya problem solving well, subjects with a dependent field cognitive style are able to solve problems carrying out all stages of Polya problem solving in the adequate category